(3ef fSH Edi Geg ef GdTYQGAs - (3GHf MHjH , CHh LYaQ GdHZOGOj,J (B245 (3g` s
(3ChdgG (B:s
(3bQCJ Ydi CNj eMeO bGd SeYJg jbQC Ydi CHj YHOGddg EHQGgje Hf eMeO GHf YQaI bGd(B: (3bQCJ Ydi KYdH(B: (3bGd CHhLYaQ Hf eMeO MHjH s
(3Yf fSNI ofbdJ ef NW GHf Lfj hUMMgG QVj GdOjf GdTGWHjs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3QhGjI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs